Innate Immune Evasion by Human Respiratory Syncytial Virus - Ouyang, Yan; Liao, Hongqun; Hu, Yan; Luo, Kaiyuan; Hu, Shaowen; Zhu, Huifang (Frontiers in Microbiology, 2022)
Respiratory syncytial virus (RSV) is the leading cause of severe respiratory infection in young children. Nearly all individuals become infected in their early childhood, and reinfections with RSV are common throughout life. Primary infection with RSV is usually involved in the symptom of bronchiolitis and pneumonia in the lower respiratory tract, which accounts for over 3 million hospitalizations and approximately 66, 000 deaths annually worldwide. Despite the widespread prevalence and high morbidity and lethality rates of diseases caused by RSV infection, there is currently no licensed RSV vaccine. During RSV infection, innate immunity plays the first line of defense to suppress RSV infection and replication. However, RSV has evolved multiple mechanisms to evade the host's innate immune responses to gain a window of opportunity for efficient viral replication. This review discusses the comprehensive interaction between RSV infection and the host antiviral innate immunity and updates recent findings on how RSV modulates the host innate immune response for survival, which may provide novel insights to find potent drug targets and vaccines against RSV.